Nurses' extended work hours: Patient, nurse and organizational outcomes - W. Kunaviktikul (2018)
© 2015 International Council of Nurses. Background: Nursing shortages have been associated with increased nurse workloads that may result in work errors, thus impacting patient, nurse and organizational outcomes. Aim: To examine for the first time in Thailand nurses' extended work hours (working more than 40h per week) and its relationship to patient, nurse and organizational outcomes. Methods: Using multistage sampling, 1524 registered nurses working in 90 hospitals across Thailand completed demographic forms: the Nurses' Extended Work Hours Form; the Patient, Nurse, Organizational Outcomes Form; the Organizational Productivity Questionnaire and the Maslach Burnout Inventory. The data were analysed using descriptive statistics, Spearman's rank correlation and logistic regression. Results: The average extend ed work hour of respondents was 18.82h per week. About 80% worked two consecutive shifts. The extended work hours had a positive correlation with patient outcomes, such as patient identification errors, pressure ulcers, communication errors and patient complaints and with nurse outcomes of emotional exhaustion and depersonalization. Furthermore, we found a negative correlation between extended work hours and job satisfaction as a whole, intent to stay and organizational productivity. Nurses who had extended work hours of > 16h per week were significantly more likely to perceive all four adverse patient outcomes than participants working an extended ≤8h per week. Limitations: Patient outcomes were measured by respondents' self-reports. This may not always reflect the real occurrence of adverse events. Conclusions: Associations between extended work hours and outcomes for patients, nurses and the organization were found. The findings demonstrate that working two shifts (16h) more than the regular work hours lead to negative outcomes for patients, nurses and the organization. Implications for nursing and health policy: Our findings add to increasing international evidence that nurses' poor working conditions result in negative outcomes for professionals, patients and health systems. Policymakers need to be aware of the issues regarding nurses' extended work hours, which has been found to contribute to burnout. Urgently, nurse and health administrators need to develop and implement appropriate nursing overtime policies and strategies to help reduce this phenomenon, including measures to overcome the nursing shortage. International Nursing Review